Institutional Trust 2008 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Gallup (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Gallup and involved 1000 individuals who answered a web survey between September 26 and October 3, 2008. The survey comprised 26 institutions/companies/media companies and political parties. The 2008 survey also included questions about the media coverage of the EU and different areas of Sweden, and how the media content influences people’s knowledge, opinions, life styles, moods, and feelings.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2008 genomfördes av TNS Gallup och omfattade 1000 personer som besvarade en nätenkät. Studien genomfördes 26/9 - 3/10 2008 och innefattade 26 institutioner/företag/medier/partier. I 2008 års undersökning ingick även frågor om mediernas rapportering om EU och olika delar av Sverige, och om hur mediernas innehåll påverkar människors kunskaper, åsikter, livsstilar, humör och känslor.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2008
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper